ITCD because of death and the conflict between the Minas Gerais legislation and the STF positioning (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present work proposes to analyze the tax on inheritances and donations, the ITCD, of Minas Gerais, in light of the Brazilian legislation and the understanding of the courts. Through the hypothetical-deductive method, basing the research on scientific bibliography, legislation and jurisprudence, it analyzes how the State of Minas Gerais has been demanding the ITCD in opposition to the understanding of the national Judiciary, and demonstrates the need for a reformulation in the state legislation, to suit national requirements.